Exploring the perceived effects of Destructive Leadership on employees' psychological empowerment: An Azerbaijan retail context - Hoffman, Ettiene Paul; Sergio, Rommel Pilapil; Chabani, Zakariya; Ahuja, Jaya (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
Azerbaijan's dynamic and diverse retail landscape is driving an escalating demand for motivated personnel, both locally and globally, to address sustainable development requirements. In competitive and demanding retail environments, the success of organizations can rely on confident, skilled, motivated, and informed employees to meet challenging business demands and inclusive growth. As Azerbaijan's retail competitive edge continues to expand, there is a heightened need for effective employer-employee interactions and strategic human capital to navigate intricate organizational hurdles. The targeted population for this study included current retail employees, and semi-structured in-depth interviews with 15 participants from 15 different retail service organizations were conducted. Hence, this research study addresses a crucial gap in leadership literature by examining the interplay between destructive leadership and employees' psychological empowerment, encompassing dimensions like meaningfulness, self-determination, competence, and impact. Employing a qualitative phenomenological approach, the study delves into the real-life experiences of employees within the Azerbaijani retail sector. The study concludes that destructive leadership can significantly hamper employees' psychological empowerment, resulting in negative impacts on their work role orientation, engagement, productivity, and commitment.